Heat transfer in the flow of a cold, axisymmetric vertical liquid jet against a hot, horizontal plate - Shu, Jian Jun (2011)
The paper considers heat transfer characteriestics of thin film flow over a hot horizontal flat plate resulting from a cold vertical jet of liquid falling onto the surface. A numerical solution of high accuracy is obtained for large Reynolds numbers using the modified Keller box method. For the flat plate, solutions for axisymmetric jets are obtained. In a parallel approximation theory, an advanced polynomial approximation for the velocity and temperature distribution is employed and results are in good agreement with those obtained using a simple Pohlhausen polynomial and the numerical solutions.